Moving cardio-oncology foward: the role of physical exercise on cardiovascular disease in breast cancer patients - Naaktgeboren, Willeke Romanie (Utrecht University, 2023)
Exercise is an increasingly recognized effective strategy to counteract cancer-related symptoms, such as cancer-related fatigue, during and shortly after chemotherapy. However, if exercise during chemotherapy has lasting effects and thus translates to fewer sequelae years after treatment has received little attention. Cardiovascular disease (CVD) is among the most prevalent yet burdensome late effects of cancer and its treatment. Evidence from animal studies almost unanimously indicates less anthracycline-associated cardiotoxicity in exercising animals than in controls. We hypothesize that accelerated cardiac chemotherapy clearance could underly exercise-mediated cardioprotection. Clinical studies were limited with small sample sizes and yielded mixed results. In a cohort of long-term breast cancer survivors, we found that higher physical activity levels were associated with better cardiac function. Results of the Pact-Paces-Heart study indicate that exercise and physical activity during chemotherapy for breast cancer were associated with better structural, but not functional, cardiac imaging parameters 8.5 years after treatment. A combined analysis of two previously performed randomized studies found that breast cancer patients with lower pre-treatment physical fitness were more likely not to complete chemotherapy as planned. This association was almost completely mitigated in patients randomized to the exercise program, while it was more pronounced in non-exercising patients. Cancer-related cognitive complaints are common in breast cancer patients treated with chemotherapy. We found that exercise during chemotherapy was not associated with better cognitive outcomes. Overall, the results of this thesis provide additional support for exercise as supportive care during cancer treatment. Future, prospectively designed exercise studies are needed to move the field of cardio-oncology forward.
Keywords: Cardio-oncology; Physical exercise; Breast cancer; Cognition; Chemotherapy completion